2014
DOI: 10.1038/ejcn.2014.271
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of maternal grain intake and serum triglyceride levels with infant birth weight: Mothers and Children’s Environmental Health (MOCEH) study

Abstract: The relationship between maternal TG levels and infant birth weight may depend on dietary grain intake and stages of pregnancy in Korean pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
1
7
1
Order By: Relevance
“…For HDL‐C, both studies reporting in T1, 6 out of 11 studies reporting in T2 and 11 out of 18 studies reporting in T3 showed an inverse association with birthweight, while 1 in T2 and 1 in T3 reported a positive association. For TG, 4 out of 5 studies reporting in T1, 10 out of 12 studies reporting in T2 and 20 out of 27 studies reporting in T3 found a positive association with birthweight, while 3 studies in T3 reported an inverse association. Of the seven studies reporting the association between maternal FFAs level in T3 and birthweight , four reported a positive association , while none reported inverse association.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…For HDL‐C, both studies reporting in T1, 6 out of 11 studies reporting in T2 and 11 out of 18 studies reporting in T3 showed an inverse association with birthweight, while 1 in T2 and 1 in T3 reported a positive association. For TG, 4 out of 5 studies reporting in T1, 10 out of 12 studies reporting in T2 and 20 out of 27 studies reporting in T3 found a positive association with birthweight, while 3 studies in T3 reported an inverse association. Of the seven studies reporting the association between maternal FFAs level in T3 and birthweight , four reported a positive association , while none reported inverse association.…”
Section: Resultsmentioning
confidence: 93%
“…Of the 13,705 unique records identified by the searches, 46 publications reporting from 42 studies were included in the review (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to other rodent studies ( 27 30 ), HF feeding even slightly reduced fetal body weight in the present study. Human studies have demonstrated that maternal blood TG levels correlate with fetal growth ( 45 47 ). Therefore, we speculate that decreased maternal blood TGs may underpin the decreased fetal growth in HF-fed rodents ( 27 30 ).…”
Section: Discussionmentioning
confidence: 99%